Annual ground temperature measurements at various depths - Florides, Georgios A.; Kalogirou, Soteris A. (My University, 2005)
The earth temperature beyond a depth of 1 meter is usually insensitive to the diurnal cycle of air temperature and solar radiation and the annual fluctuation of the earth temperature extends to a depth of about 10 meters. In order to study the fluctuations of the ground temperature with depth we have installed a 50m deep U-tube in the ground equipped with thermocouples at various depths. The measured temperatures indicate that the short-period temperature variations are prominent to a depth of approximately 0.5 m. Because of the high thermal inertia of the soil, the temperature fluctuations at the surface of the ground are diminished as the depth of the ground increases. The annual temperature variation of the ground at a depth of 3m is between 15 to 25°C while at a depth of 25m is negligible and the temperature remains constant at about 22°C. The temperature measurements are compared to the calculated values resulting from simulations performed with TRNSYS.
Keywords: Ground temperature; Measurement; Kasuda formula